Integrating Google Earth into Scale Learning: A Learning Trajectory Through Rice Field Size Exploration - Sari, Filian Yunita; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Susanti, Ely (Edumatica : Jurnal Pendidikan Matematika, 2025)
Students' difficulties in understanding the concept of scale, both conceptually and applicative, are caused by learning that is still abstract and has minimal connection to the real context, so it is necessary to present learning that is more meaningful and applicable. This study aimed to produce a learning trajectory for the concept of scale through rice field size exploration using Google Earth. The approach employed was design research of validation studies type, which encompassed three stages: design preparation, design experiment, and retrospective analysis. The study was conducted at State Junior High School 1 Belitang involving two classes, eight students from class VII.3 and thirty-one students from class VII.4. Data was collected through student activity sheets, observations, and interviews, then analyzed qualitatively using descriptive methods with triangulation techniques. The results showed that learning trajectory for the concept of scale starting from measuring images, comparing sizes in images and actual sizes, making model representations through double number lines, discussing the concept of scale and applying scale in real calculations. The study implied the importance of contextual digital media in fostering meaningful and concrete understanding of mathematical concepts.